2018
DOI: 10.1210/jc.2017-02669
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Denosumab on Bone Histomorphometry and Mineralization in Women With Postmenopausal Osteoporosis

Abstract: ContextDenosumab is a potent antiresorptive agent that reduces fractures in postmenopausal women with osteoporosis.ObjectiveDetermine effects of up to 10 years of denosumab on bone histology, remodeling, and matrix mineralization characteristics.Design and SettingInternational, multicenter, randomized, double-blind trial [Fracture Reduction Evaluation of Denosumab in Osteoporosis Every 6 Months (FREEDOM)] with a long-term open-label extension.PatientsPostmenopausal women with osteoporosis (92 women in FREEDOM,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 46 publications
6
33
0
1
Order By: Relevance
“…Histomorphometric studies performed on transiliac bone biopsies in women with postmenopausal osteoporosis have shown a marked reduction in bone remodeling, both resorption and formation, in cancellous bone after 2 and 3 years of denosumab . This decreased cancellous bone turnover is maintained after an extension of the treatment up to 5 and 10 years . The analysis of bone biopsies obtained approximately 2 years after discontinuation of denosumab treatment confirmed that these effects are reversible, which is consistent with the known mechanism of action of denosumab.…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…Histomorphometric studies performed on transiliac bone biopsies in women with postmenopausal osteoporosis have shown a marked reduction in bone remodeling, both resorption and formation, in cancellous bone after 2 and 3 years of denosumab . This decreased cancellous bone turnover is maintained after an extension of the treatment up to 5 and 10 years . The analysis of bone biopsies obtained approximately 2 years after discontinuation of denosumab treatment confirmed that these effects are reversible, which is consistent with the known mechanism of action of denosumab.…”
Section: Introductionsupporting
confidence: 71%
“…(9) This decreased cancellous bone turnover is maintained after an extension of the treatment up to 5 and 10 years. (10,11) The analysis of bone biopsies obtained approximately 2 years after discontinuation of denosumab treatment confirmed that these effects are reversible, (12) which is consistent with the known mechanism of action of denosumab.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…It may, therefore, be that BMSi measurements capture the observed increases in MM by antiresorptive therapies. Notably, prolongation of treatment with bisphosphonate, as in the FLEX study with alendronate, is not associated with continuous increase in MM [36] indicating that the amount of mineral taken up by the matrix in non-pathological mineralisation is limited, or self-regulated; this finding is similar to the observed plateau of bone matrix mineralisation between 5 and 10 years treatment of patients with osteoporosis with denosumab [37] and may explain the lack of further increases in BMSi values when these reach normal levels shown in our study.…”
Section: Discussionsupporting
confidence: 52%
“…Thus, although both drugs inhibit bone resorption, long-term bisphosphonate therapy is associated with little or no reduction in the number of osteoclasts, but with abnormal appearing osteoclasts that include giant, hypernucleated, detached osteoclasts 45 . By contrast, DMAb markedly reduces osteoclast numbers on all bone surfaces 46 . As such, bisphosphonates and DMAb may have differing effects on osteoclast DPP4 production, and this possibility warrants further investigation.…”
Section: Discussionmentioning
confidence: 90%